The role of effectors in nonhost resistance to filamentous plant pathogens - Stam, Remco; Mantelin, Sophie; McLellan, Hazel; Thilliez, Gaëtan (Frontiers in Plant Science, 2014)
In nature, most plants are resistant to a wide range of phytopathogens. However, mechanisms contributing to this so-called nonhost resistance (NHR) are poorly understood. Besides constitutive defences, plants have developed two layers of inducible defence systems. Plant innate immunity relies on recognition of conserved pathogen-associated molecular patterns (PAMPs). In compatible interactions, pathogenicity effector molecules secreted by the invader can suppress host defence responses and facilitate the infection process. Additionally, plants have evolved pathogen-specific resistance mechanisms based on recognition of these effectors, which causes secondary defence responses. The current effector-driven hypothesis is that nonhost resistance in plants that are distantly related to the host plant is triggered by PAMP recognition that cannot be efficiently suppressed by the pathogen, whereas in more closely related species, nonhost recognition of effectors would play a crucial role. In this review we give an overview of current knowledge of the role of effector molecules in host and nonhost resistance and place these findings in the context of the model. We focus on examples from filamentous pathogens (fungi and oomycetes), discuss their implications for the field of plant-pathogen interactions and relevance in plant breeding strategies for development of durable resistance in crops.